Volume of distribution as an early predictor of vancomycin-induced AKI in critically ill patients - Ghasemiyeh, Parisa; Vazin, Afsaneh; Zand, Farid; Mohammadi-Samani, Soliman (Acta Biomedica Atenei Parmensis, 2023)
-